Numerical investigation of the finite superelement method for the 3D elasticity problems - Galanin, Mikhail; Lazarev, Mikhail; Savenkov, Evgeny (Mathematical Modelling and Analysis, 2007)
The results of numerical investigation of the Finite Superelement Method (FSEM) for the solution of 3D elasticity problems are given. A definition of FSEM is proposed, and the general theory is briefly explained. Then the variants of FSEM are considered for the model problem. Their comparative analysis is being carried out. These variants are based on the finite element interpolation techniques on superelements boundaries. FSEM and FEM efficiency comparison is presented for the model problem. Quantative error data are obtained. A certain example of a 3D elasticity problem is considered in conclusion. A notable advantage of a higher degree FSEM approximation technique is illustrated.First Published Online: 14 Oct 2010